Day 2 IFPRI Presentations for 2023 CGIAR GENDER-ICAR Conference - Alvi, Muzna; Beniwal, Ezaboo; Singh, Tushar; Raja, Sehrish; Johnson, Nicky; Vemireddy, Vidya; Seymour, Greg; Heckert, Jessica; Cheong, Yuk Fai; Doss, Cheryl; Faas, Simone; Hassan, Imrul; et al. (2023)
IFPRI is participating in the 2023 annual CGIAR Gender Research Conference. This conference is co-hosted by the CGIAR GENDER Impact Platform and the Indian Council of Agricultural Research (ICAR) and will take place in New Delhi, India, on October 9-12, 2023.